Innovating feeding strategies in dairy sheep farming can reduce environmental impact of ewe milk. Issue 1 (1st January 2021) - Bosco, Simona; Volpi, Iride; Cappucci, Alice; Mantino, Alberto; Ragaglini, Giorgio; Bonari, Enrico; Mele, Marcello
Abstract: Dairy sheep systems are relevant for the economy of many rural areas of the Mediterranean Basin and the optimisation of their productive factors is necessary to improve their competitiveness and to reduce their environmental impact. The objective of this study was to assess, through a farm-scale life cycle assessment (LCA) approach, the potential of reducing environmental impacts on ewe milk of an innovative farming system (IF), based on the adoption of a precision feeding approach to improve milk production and quality, compared with a conventional farming system (CF) in dairy sheep farms in Tuscany region, Italy. The LCA analysis was carried out through a cradle-to-farm-gate LCA, comparing three conventional farms with three innovative farms, using 1 kg of fat protein corrected milk (FPCM) as a functional unit. The Small Ruminants Module of Nutritional Dynamic System (NDS) software was used to estimate methane emissions due to enteric fermentation. The introduction of precision feeding strategy reduced the environmental impacts of ewe milk as a consequence of the increased milk production efficiency (+50%). Indeed, the environmental impact of ewe milk was reduced in IF by 42% as the average of the impact categories being significantly different between the two farming systems. Highlights: Precision feeding is recognised as a strategy to mitigate the environmental impacts of ruminant production. Dairy sheep innovative farms (IF), using a precision feeding approach, were compared with conventional farms (CF). Environmental impacts of ewe mik were assessed through an LCA approach and a mechanistic model for ruminant diet formulation and evaluation. Precision feeding improved milk production efficiency (+50) and lowered environmental impacts. Environmental impact of ewe milk was significantly reduced in IF by 42% in eight impact categories out of 15.